2014
DOI: 10.7860/jcdr/2014/9649.5188
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profile and Metabolic Syndrome Status in Patients with Oral Lichen Planus, Oral Lichenoid Reaction and Healthy Individuals Attending a Dental College in Northern India - A Descriptive Study

Abstract: There may be an association between chronic inflammation and dyslipidemia that increases the risk for cardiovascular disease. OLP and OLR patients have increased serum cholesterol and LDL-C when compared to normal adults. Further research on lipid levels in OLR are required to establish the findings of this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 17 publications
4
32
4
Order By: Relevance
“…6,9,10,16–18 The authors also reported a comparatively lower mean HDL‐C level of 32.2 ± 6.4 mg/dl . The HDL‐C levels in patients with LP reported by other studies ranged from 42.4 ± 0.21 to 59.8 ± 14.6 mg/dl . Mean total cholesterol and LDL‐C levels in this study were also relatively higher than those from other studies.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…6,9,10,16–18 The authors also reported a comparatively lower mean HDL‐C level of 32.2 ± 6.4 mg/dl . The HDL‐C levels in patients with LP reported by other studies ranged from 42.4 ± 0.21 to 59.8 ± 14.6 mg/dl . Mean total cholesterol and LDL‐C levels in this study were also relatively higher than those from other studies.…”
Section: Discussionsupporting
confidence: 48%
“…Table 1 summa-rizes the study population characteristics in each study. 6,9,10,[16][17][18][19] All but one study identified cases of LP through histological confirmation. Three studies were deemed to be high quality based on the aforementioned validated five-point scale.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…While studies on the association of level of prevalence of MS in mucosal than in cutaneous LP as well as in patients with longer disease duration. Other investigators have shown that there is an association between oral LP and oral lichenoid reaction and MS (20). It should also be mentioned that various clinical presentations of LP are in association with different risks of MS.…”
Section: Discussionmentioning
confidence: 93%
“…AriasSantiago et al reported a significant prevalence of serum lipid derangement in all parameters including TG, LDL-C, HDL-C, Chol, Total cholesterol/HDL-C, and LDL-C/HDL-C ratios among LP patients in comparison with controls (21). Oral LP and oral lichenoid reaction have also been associated with significant dyslipidemia (20). Other authors, however, did not find abnormal lipid levels in LP (18,35).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation